1995
DOI: 10.1111/j.1365-2516.1995.tb00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose activated factor IX complex concentrates (FEIBAR) for post‐operative haemostasis in a patient with high responding factor VIII inhibitors

Abstract: Replacement therapy in patients with severe haemophilia A is associated with the development of inhibitory antibodies in about 15% [1,2]. The presence of inhibitors of factor VIII greatly complicates and compromises the treatment of these patients because of the lack of any completely satisfactory product to treat them. Haemostatic management for surgery in patients with inhibitors is very difficult. A product frequently used to treat bleeding episodes in such patients is prothrombin complex concentrate (PCC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…This may have been due to the lower doses used. We have previously shown that low doses of activated prothrombin complex can be used for post‐operative haemostasis in severe haemophilia with high‐titre inhibitors without inducing major coagulopathies [6].…”
Section: Discussionmentioning
confidence: 99%
“…This may have been due to the lower doses used. We have previously shown that low doses of activated prothrombin complex can be used for post‐operative haemostasis in severe haemophilia with high‐titre inhibitors without inducing major coagulopathies [6].…”
Section: Discussionmentioning
confidence: 99%
“…, 1998, 2000a,b) with or without FEIBA in these patients, with satisfying results. Bhave et al. (1995) successfully used low levels of FEIBA in a patient with inhibitor to secure surgical haemostasis.…”
Section: Inhibitor Development In Haemophiliacsmentioning
confidence: 99%
“…A few surgical experiences in haemophilia patients from India are available in the literature [4–7], one of which voiced concern regarding the possibility of inhibitor development in the postoperative period [4]. However, development of inhibitor for the first time in the postoperative period was reported in none of the series, although operative management of patients with known inhibitor has been reported [7]. In the present communication, we describe six patients who developed inhibitor postoperatively.…”
Section: Introductionmentioning
confidence: 95%
“…In this situation, it is natural that quite a few patients with severe haemophilia A may be receiving relatively generous amounts of factor concentrate for the first time at or during the time of surgical interventions, which will predispose the susceptible patients to develop inhibitors during the postoperative period, making their management costlier and also prolonging their hospital stay. A few surgical experiences in haemophilia patients from India are available in the literature [4–7], one of which voiced concern regarding the possibility of inhibitor development in the postoperative period [4]. However, development of inhibitor for the first time in the postoperative period was reported in none of the series, although operative management of patients with known inhibitor has been reported [7].…”
Section: Introductionmentioning
confidence: 99%